The provisions on education in the new constitution a historico-legal study - Diaz, Clodualdo C. 1927- (1981)
The 1973 Constitution (1) contains additional requirements to make the educational system more responsive to national needs and aspirations, (2) is more cognizant of freedom and research, (3) emphasizes rights and obligations of students, (4) stresses free public elementary and secondary education, (5) provides educational opportunities for adults, out of school youth and poor but deserving students, (6) Filipinizes almost all private educational institutions, (7) regulates religious instruction, (8) emphasizes the role of science and technology in national development and protects inventions and original works, (9) mandates the development of Filipino as the national language, and (10) taxes the use of land for educational purposes unless private educational institutions are converted into non-profit foundations.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Quezon City.
Vita.
Keywords: Educational law and legislation -- Philippines; Education and state -- Philippines; Education -- Aims and objectives. -- Philippines